Dietary patterns and recurrent pregnancy loss: a comparison of the American Heart Association diet, Mediterranean diet and others - Ma, Yan; Li, Qianqian; Li, Rui; Lu, Liangjing (Frontiers in Nutrition, 2025)
BackgroundRecurrent pregnancy loss (RPL) presents a major challenge in reproductive medicine, with lifestyle factors, especially dietary patterns, potentially influencing pregnancy outcomes. This study aimed to explore the relationship between adherence to preconception dietary patterns and pregnancy outcomes in women with RPL.MethodsThe study included 475 women with RPL at Renji Hospital, Shanghai Jiao Tong University School of Medicine. Participants completed a semi-quantitative food frequency questionnaire (FFQ) to assess adherence to six pre-defined dietary patterns at preconception: the American Heart Association Diet (AHA), Trichopoulou Mediterranean Diet (TMED), Panagiotakos Mediterranean Diet (PMED), Alternate Mediterranean Diet (AMED), Healthy Eating Index-2015 (HEI-2015), and Dietary Approaches to Stop Hypertension (DASH). Pregnancy loss, gestational diabetes mellitus (GDM), hypertensive disorders of pregnancy (HDP), and other adverse pregnancy outcomes (APO) (e.g., preterm birth, low birth weight) were ascertained using medical records.ResultsSignificant associations were observed between adherence to the AHA diet and reduced risks of pregnancy loss [adjusted RR (95% CI), highest quartile (Q4) vs. lowest quartile (Q1): 0.36 (0.17, 0.78), P-trend = 0.043], GDM [adjusted RR (95% CI), highest quartile (Q4) vs. lowest quartile (Q1): 0.28 (0.10, 0.75), P-trend = 0.006], HDP [adjusted RR (95% CI), highest quartile (Q4) vs. lowest quartile (Q1): 0.12 (0.03, 0.57), P-trend = 0.008], and other adverse pregnancy outcomes [adjusted RR (95% CI), highest quartile (Q4) vs. lowest quartile (Q1): 0.04 (0.01, 0.35), P-trend = 0.001]. Similar associations were found for the AHEI, AMED, and TMED diets regarding pregnancy loss, GDM, and HDP, while the PMED and DASH diets showed no significant associations. Additionally, higher levels of moderate-to-vigorous physical activity and lower energy and fat intake were associated with increased live birth rates.ConclusionGreater adherence to the AHA diet during the preconception period was linked to lower risks of pregnancy loss, and adverse pregnancy outcomes. These findings support the AHA diet for patients with recurrent pregnancy loss, indicating that healthy dietary patterns may improve pregnancy outcomes and highlight the need for further research on their impact on fertility.